Edible Flowers Extracts as a Source of Bioactive Compounds with Antioxidant Properties—In Vitro Studies - Karolina Jakubczyk; Agnieszka Łukomska; Izabela Gutowska; Joanna Kochman; Joanna Janił; Katarzyna Janda (Applied Sciences, 2021)
Edible plants began to play an important role in past decade as a part of therapy, a recovery process or a healthy life style. The availability and relatively low price of the raw material, as well as proven bioactive health benefits, are key to consumers’ choice of nutrients. The red clover (Trifolium pratense) is a popular plant with healthy properties such as antiseptic and analgesic effects. The less known white clover (Trifolium repens), a fodder and honey plant, has anti-rheumatic and anti-diabetic properties. Both species may serve as a potential source of bioactive substances with antioxidant properties as a food additive or supplement. The study material consisted of flower extracts of Trifolium repens and Trifolium pratense. The total content of polyphenols and DPPH (2.2-diphenyl-1-picrylhydrazyl) and ferric reducing antioxidant power (FRAP) were measured using spectrophotometry methods. Oxidative stress in THP1 cells was induced via sodium fluoride. Subsequently, flower extracts were added and their influences on proliferation, antioxidant potential and the activity of antioxidant enzymes were evaluated. The extracts have a high total content of polyphenols as well as high antioxidant potential. We also demonstrated positive extracts impact on cells proliferation, high antioxidant potential and increasing activity of antioxidant enzymes on cell cultures under high oxidative stress induced by fluoride. Both red clover and the less known white clover may serve as valuable sources of antioxidants in the everyday diet.